PENGARUH MODEL PJBL BERBASIS ETNOSAINS TERHADAP KEMAMPUAN BERNALAR KRITIS SISWA PADA PEMBELAJARAN IPAS KELAS IV SD NEGERI 1 CIBEUREUM - Novia Anggraini; Agatha Kristi Pramudika Sari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to determine the effect of implementing the Ethnoscience-Based PJBL Model on students' critical reasoning abilities in class IV science and science subjects at Cibeureum 1 State Elementary School. The background to this research is the problem of students' lack of ability in critical reasoning in elementary schools which is still low. Therefore, a learning model is needed to improve students' critical reasoning abilities, one of which is through the Ethnoscience-Based PJBL Model. The method used in this research is quantitative with a Quasi Experimental Design research design, Nonequivalent Control Group Design model. The data collection techniques used are observation, tests and documentation. The instruments used were a pre-test and post-test to determine students' critical reasoning abilities. The population in this study was all students in class IV elementary school for the 2023-2024 academic year, totaling 45 students. The samples were class IV A students as the control class, totaling 22 students and class IV B as the experimental class, totaling 23 students. The data analysis techniques of this research are Normality Test, Homogeneity Test, and Hypothesis Test. Thus, this research can be concluded that the application of the Ethnoscience-Based PJBL Model has an effect on the critical reasoning abilities of class IV students at Cibeureum 1 State Elementary School. So this research is expected to be able to improve students' critical reasoning abilities in grade IV science learning at Cibeureum 1 State Elementary School.